ANALISIS KEBUTUHAN MEDIA BERBASIS IT PADA MATA PELAJARAN FIQIH SISWA KELAS X - Rusma Hidayati; Siti Aisyah (MUMTAZ : Jurnal Pendidikan Agama Islam, 2024)
This article is composed with the aim of understanding the analysis of IT-based media needs in teaching Islamic jurisprudence (fiqh) to 10th-grade students at MA Muslimat NU Palangka Raya. The researcher employs the research method known as Research and Development (R&D). In this study, the 4D development model is also utilized. The focus of the research is on fiqh education, which encompasses the study of Islamic teachings ordained by Allah SWT. The researcher aims to identify the needs of students in the learning process. This investigation delves into IT-based media, which can serve as a tool to aid teachers and students in the learning process, making it more accessible and straightforward. The article discusses issues encountered in the field, and the research methodology involves distributing questionnaires at one of the schools in Palangka Raya, namely MA Muslimat NU Palangka Raya, with 10th-grade students as respondents. The analysis conducted in the field indicates that students require learning media, such as IT-based tools, to enhance their understanding in the learning process.